2008
DOI: 10.1111/j.1467-8268.2008.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Interest Rate Spreads in Ghana*

Abstract: The question of the optimal spread between bank lending rates and rates that banks pay on deposits, which is fair to bankers, depositors and borrowers, has dogged economies for some time. In Ghana, there is widespread perception that the spread is too wide. Bankers, on the other hand justify the spread on the basis of economic variables that affect them. This paper contributes to the literature by identifying, in the case of Ghana, the short-run response of the net interest margin of banks to changes in banksp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 13 publications
6
52
0
Order By: Relevance
“…Kouki and Al-Nasser (2014) found an average market power index of within 58% and 74% within the period 2005-2010. Studies by Aboagye et al (2008), Amidu (2013) and Ariss (2010) found a varying degree of market power in a number of countries that were studied.…”
Section: Econometric Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Kouki and Al-Nasser (2014) found an average market power index of within 58% and 74% within the period 2005-2010. Studies by Aboagye et al (2008), Amidu (2013) and Ariss (2010) found a varying degree of market power in a number of countries that were studied.…”
Section: Econometric Analysismentioning
confidence: 97%
“…To answer this question, this study will compute the bank level competition index of the SSA commercial banks using Lerner index 2 This method has been widely used in literature and in some studies of the degree of competitiveness of African banks, (see Aboagye et al (2008) in Ghana, for one country study of SSA and Kouki and Al-Nasser (2014) for a panel of 31 countries in Africa). This study adopts the Lerner index because among its contemporaries, it is one of the most efficient competition measures following the outcome of the correlation of all indicators by Liu et al (2013).…”
Section: Model Specificationmentioning
confidence: 99%
“…Angbazo (1997), who first argued for the inclusion of credit risk in this type of analysis, made the case for a positive coefficient since banks with poor portfolios would be expected to charge higher margins. Subsequently, researchers have found both positive (Maudos andFernádez de Guevera, 2004, andChirwa andMlachila, 2004) and negative (Williams, 2007, andAboagye et al, 2008) coefficients.…”
Section: Results: Overall Samplementioning
confidence: 99%
“…A number of proxies have been used in the literature with mixed results -Williams (2007) used measures of retail activity and found positive but insignificant coefficients; Maudos and Fernández de Guevera (2004) used measures of bank size and found negative and significant coefficients; Chirwa and Mlachila (2004) used market share of deposits and found the coefficient to be negative and insignificant, while Aboagye et al (2008) found positive and significant coefficients using total assets.…”
Section: Notesmentioning
confidence: 99%
“…The spread was found to increase with an increase in market power, the regulated savings deposit rate, real GDP growth, reserve requirements, provision for loan losses and operating costs. Aboagye, et al, (2008) studied the response of net interest margin of banks to changes in factors that are bank-specific, banking industry specific and Ghanaian economy macroeconomic factors. It was found that an increase in the following factors increases the net interest margin of banks: bank market power (or concentration), bank size, staff costs, administrative costs, extent to which a bank is risk averse and inflation.…”
Section: Empirical Literaturementioning
confidence: 99%